From virus to infovirus : Views on the pandemic from biopolitics, theory of exception and psychopolitics, to technopolitics - Marín-Casanova, José Antonio (Revista Ethika+, 2020)
Study about the different perspectives of understanding the policies of life surveillance and of social control when intelectually approaching the current pandemic. It emphasizes that all these policies are implemented today through ICTs, extending the digital domain over the offline world and getting pandemics into technopandemics. This is how they all turn out, biopolitics, theory of the exception and psychopolitics, conceptually surpassed by technopolitics. Technopolitics is the political-social form of onlife, the practice of an infodemic power, which uses informational techno-persons, who are neither individuals nor political subjects, to control and subdue the offlife.